Critical Thinking versus Neurosexism - Reverter-Bañón, Sonia (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
The aim of this paper is to offer a view of the assumptions that guide the practice of claiming sex differences in the brain. After the realization that much of the research and publication of neuroscientific findings assume such a difference, we found a great deal of what has been called neurosexism. As a way to overcome it and from a feminist theory with a political commitment we propose a critical approach to the neurosciences. This is understood as a reflective collaboration between disciplines that could provide a framework for overcoming prejudices in thinking and designing science.
Keywords: neurosexism; sexual differences; critical neurosciences; neuroethics; sex/gender; pseudoscience.